Plasma reforming of ethanol in DGCLW discharge - Yukhymenko, V.V.; Chernyak, V.Ya.; Olszewski, S.V.; Sidoruk, S.M.; Demchina, V.P.; Levko, D.S.; Shchedrin, A.I. (Вопросы атомной науки и техники, 2011)
This paper presents the results of experimental and theoretical investigations of the process of non-thermal plasmaassisted
reforming of aqueous ethanol solutions in the dynamic plasma liquid systems using the DC electric discharges
in a gas channel with liquid wall. The experiments show possibilities and efficiency of low-temperature plasmachemical
conversion of liquid ethanol into hydrogen-rich synthesis gas in different regimes. The numerical modelling
clarifies the nature and explains the kinetic mechanisms of non-equilibrium plasma-chemical transformations in the
plasma-liquid systems in different modes. Представлено результати експериментальних та теоретичних досліджень процесів нетермічного реформінгу,
що підтримується плазмою, водних розчинів етанолу в динамічній плазмово-рідинній системі з використанням
електричного розряду постійного струму в газовому каналі з рідкою стінкою (РГКРС). Експерименти
показують можливість та ефективність низькотемпературної плазмохімічної конверсії рідкого етанолу в
збагачений воднем синтез-газ в різних режимах. Чисельне моделювання висвітлює природу та пояснює
кінетичні механізми нерівноважних плазмохімічних перетворень в плазмово-рідинній системі в різних
режимах. Представлены результаты экспериментальных и теоретических исследований процессов нетермического
реформинга, поддерживаемого плазмой, водных растворов этанола в динамической плазменно-жидкостной
системе с использованием электрического разряда постоянного тока в газовом канале с жидкой стенкой
(РГКЖС). Эксперименты показывают возможность и эффективность низкотемпературной плазмохимической
конверсии жидкого этанола в обогащенный водородом синтез-газ в разных режимах. Численное моделирование
показывает природу и объясняет кинетические механизмы неравновесных плазмохимических преобразований в
плазменно-жидкостной системе в разных режимах.